The well-protected domains: ideology and the legitimation of power in the Ottoman Empire 1876-1909 - Deringil, Selim (Tauris, 1999)
ch. 1.Long live the Sultan!: symbolism and power in the Hamidian Regime --ch. 2.Ottomanization of the Sȩriat --ch. 3.To enjoin the good and to forbid evil: conversion and ideological reinforcement --ch. 4.Education: the answer to all evil? --ch. 5.They confuse and excite minds: the missionary problem --ch. 6.Ottoman image management and damage control --ch. 7.Ottoman 'self portrait' --ch. 8.Conclusion.